Resource potential of the enterprise - Kopytsia , A. O.; Pererva, P. G. (Національний технічний університет "Харківський політехнічний інститут", 2023)
It is proved that the potential of an enterprise can be considered from the following two positions: resource - as a set of resources and links between them; functional - as a set of functions that ensure the realization of abilities and opportunities.
Ресурсний потенціал підприємства
Keywords: potential; material resources; industrial enterprises; efficiency